MANAGEMENT OF MARKETING RISKS ON THE AGRICULTURAL PRODUCTS MARKET - Квасова, Людмила; Курбацька, Лариса; Діхтяр, Іван (SWorldJournal, 2024)
The agricultural products market is inherently characterized by a multitude of risks that can significantly impact marketing strategies and overall profitability. This article explores the management of marketing risks within this sector, emphasizing the